Lower to Mid-Pliocene pollen data from East African hominid sites, a review - (:unkn) unknown (My University, 2021)
This paper presents fossil pollen data (39 samples) available for the Lower Pliocene outcrops at five hominid sites in East Africa located within the intertropical region between 3° South to 11° North. They are dated from 4.2 to 2.95 millions years (Ma). Most of these data were obtained many years ago, except one additional pollen assemblage recently obtained in the Woranso-Mille area of the Lower Awash valley, Ethiopia. In East Africa, Plio-Pleistocene sedimentary sequences are internationally renowned for the continuous palaeo-anthropological researches pursued for decades, following the discoveries of preserved remains of fossil hominins associated to a rich, diversified and abundant mammalian fauna. As a result of these new discoveries, geological studies have continued, being connected to following field expeditions and exploration of new sites in the Ethiopian Rift. We present here the revised geological context, adding chronological precision to previous age constraints of the original pollen data. For each terrestrial Pliocene site, we also include some comments regarding the significance of pollen counts and briefly discuss their interpretation for reconstructing past vegetation, environment, and inferred climatic parameters at the studied hominin sites.
Keywords: African Research